Quality enhancement of software maintainability evaluation model via capability maturity model integration - Hassan, Al-Ahmad Haneen (2015)
The enhancement of software maintenance process is one of the most rapidly growing concerns for many reasons such as successful delivery of projects and organization management. Software maintenance companies are reluctant to implement process improvement models and procedures because of their complex construction and challenging implementation techniques. It has been observed that the enhancement efforts are based on process development frameworks which are considered normally for large organizations. The Capability Maturity Model Integration (CMMI) enables companies and organizations to enhance presentation and rate the maturity of their level of process. This thesis focuses on classifying the significant process areas and components for software maintenance improvement and provides best performance observation for the enhancement process of which that can be applied in small organizations. The main objective of this study is to establish a new predictive model by reducing the CMMI level maintenance process integrated with agent tools. It also aimed to improve the existing model of CMMI for multi agent system (MAS) in the collaborative software maintenance environment. This thesis formulated its research objectives through relevant literature and organized reviews of CMMI and Software Performance Indicator (SPI). The study was developed based on the CMMI process reports. The investigation of the study was divided into 4 phases based on objective directions to obtain the results. The new mapping of maturity level process areas and problems is completed by analyzing CMMI process and specific practices. This research has obtained a significant finding: the establishment of a new predictive model which reduces the CMMI level maintenance process, integrated with agent tools for process enhancement. The conclusions of this study measured the performance of the improved CMMI maintenance process and defined that the existing CMMI methods for advance process just provided the controlling principles to succeed the maturity of the software maintenance process. Finally, the new integrated model based on the proposed components with software maintenance indicates a high reliability data of 0.82 and Cronbach alpha of 0.94 as an output of questionnaire design according to proposed modification.